Formación docente en el profesorado de historia Un ámbito en conflicto - ARRONDO, Cristina Comp.; BEMBO, Sandra Comp.; MONTERO, Lourdes Prol.; VEZ, José Manuel Prol. (HOMO SAPIENS, 2001)
CONTENIDO : LOPEZ FACAL, RAMON; ARMAS CASTRO, XOSE; SHAVER, JAMES P.; BENEJAM ARGUIMBAU, PILAR; MAESTRO GONZALEZ, PILAR; AUDIGIER, FRANCOISE